Perbandingan Hasil Belajar Biologi Siswa Antara Penggunaan Model Pembelajaran Kooperatif Tipe Bertukar Pasangan dengan Model Pembelajaraan Kooperatif STAD Pada Kelas VII SMP Negeri 24 Makassar - Musyafar, .; Hastuti, . (bionature, 2009)
This research aim to know the comparison between the result of the student’s studying that is learned by using exchange couple type of cooperative learning model with STAD (Student Team Achievement Division) type of cooperative learning model for class VII State junior high school no 24 of Makassar. This research is included of Queasy Experimental research with post test group only design where class VII.7 as 1st experiment and class VII.8 as 2nd experiment class. This research is done in three times of learning process meeting and once evaluation test. Taking data is done by using the test of biology studying result and then analyzed descriptive and inferentially. The result is average value in the 1st experiment class is 62,35 and for  2nd experiment class is 72,38 and after hypothesis test is done with using t-test, so obtained thitung is 2,81 and ttabel 1,99. This result shows that there is difference of result student’s biology studying between the using of exchange couple type of cooperative learning model with STAD (Student Team Achievement Division) type of cooperative learning model, where the result of student’s studying that use STAD type of cooperative learning model is higher than exchange couple type of cooperative learning model.   Keywords: exchange couple type of cooperative learning model, STAD (Student Team Achievement Division), result of studying.